Fatal X-linked agammaglobulinemia complicated by septic shock: a case report and comprehensive review of novel BTK mutations - Wu, Piaopiao; You, Wei; Liu, Wentong; Luo, Ni; Xu, Jiayue (Frontiers in Immunology, 2025)
X-linked agammaglobulinemia (XLA) is a rare primary immunodeficiency disorder caused by mutations in the Bruton tyrosine kinase (BTK) gene. This article presents a fatal case of a 20-year-old male with XLA complicated by septic shock due to Pseudomonas aeruginosa infection, highlighting two novel BTK insertion mutations in exon 15 (NM_000061.3 exon15:c.1561insG and c.1565insTAGAA). Concurrently, we provide a systematic review of XLA’s genetic basis, clinical manifestations, diagnostic challenges, and therapeutic advancements. The patient’s delayed diagnosis, lack of immunoglobulin replacement therapy, and fatal outcome underscore the importance of early genetic screening and standardized management. This case and review aim to enhance clinical awareness and emphasize the integration of genetic diagnostics into routine practice for primary immunodeficiencies.